Explore the Usefulness of Concurrent Chemotherapy in Stage II Nasopharyngeal Carcinoma: A Retrospective Study - Li, Pei-Jing; Lai, Yu-Lin; He, Fang; Chen, Yuan-Yuan; Gu, Zhuo-Sheng; Luo, Wei; Zhang, Qun (Frontiers in Pharmacology, 2021)
Objective: This study aims to compare the treatment outcomes of concurrent chemoradiotherapy (CCRT) versus radiotherapy (RT) alone in stage II nasopharyngeal carcinoma (NPC) patients. Methods: We retrospectively collected 601 stage II NPC patients treated in two hospitals between June 2003 to June 2016. All patients were divided into the CCRT group (n = 255) and the RT group (n = 346). Overall survival (OS), locoregional failure-free survival (LRFFS), progression-free survival (PFS), and distant metastasis-free survival (DMFS) were assessed using the Kaplan-Meier method. The log-rank test was used to compare the differences between the groups. The Cox-regression hazards model was performed to determine potential prognostic factors. Results: The median follow-up was 99 months. No significant difference was found in locoregional recurrence, distant metastasis, disease progression, and death between the two groups (all p > 0.05). In univariate analysis, the 5-years OS, PFS, LRFFS, and DMFS had no significant differences between the CCRT and RT groups (all p > 0.05). Two-dimensional radiotherapy (2DRT) sub-analysis showed that CCRT remarkably increased DMFS, PFS, and OS rates (all p < 0.05) but not LRFFS (p = 0.258) compared with RT alone. While intensity-modulated radiotherapy (IMRT) sub-analysis showed that the prognosis of the two groups had no significant differences (all p > 0.05). In multivariate analyses, age was significantly and inversely related to OS, PFS, LRFFS, and DMFS. IMRT was an independent favorable factor for improving LRFFS, PFS, and OS. Concurrent chemotherapy was an independent protective factor for DMFS. Conclusion: In the context of 2DRT, it is definite that concurrent chemotherapy provides survival benefits for patients with stage II NPC. While in the IMRT era, the impact of chemotherapy on survival in patients with stage II NPC is weakened. Prospective randomized controlled studies are required to confirm these results.